Kerajinan Sarung Tenun Goyor Dan Pengaruhnya Terhadap Sosial-Ekonomi Masyarakat Wanarejan Utara Pemalang 2002-2017 - Alamsyah, Alamsyah; Aniskuri, Lulu Fitria (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2021)
Goyor Woven Sarong Industry in North Wanarejan Village, Pemalang, was introduced by Tasman in 1942. At that time, the tool used was a non-machine weaving tool (ATBM). The people were then interested and followed in Tasman's footsteps to become weaving artisans. From 1942 to 1986, the existence of the handicraft industry was not constant; in 1987, the woven sarong industry started to rise, marked by the emergence of the home industry. In 2002, when North Wanarejan village was formed, the weaving industry developed significantly, marked by an increase in the number of weaving entrepreneurs. In 2017, North Wanareja was designated as a Tourism Village called â€œKate Sargoyâ€. The Goyor woven sarong industry has had a positive economic and social impact in North Wanarejan. Many people work in the woven sarong industry. The workers earn higher wages than the Regional Minimum Wage (UMR) in Pemalang. They gain welfare while working in this sarong industry. The woven sarong industry also encourages the growth of a close relationship between employers and workers. The existence of this industry changes the women's role to become more productive.